Feasibility of platelet marker analysis in ischemic stroke patients and their association with one-year outcome. A pilot project within a subsample of the Stroke Induced Cardiac Failure in Mice and Men (SICFAIL) cohort study. (4th July 2022) - Seyhan, Mert; Ungethüm, Kathrin; Schuhmann, Michael K.; Mackenrodt, Daniel; Rücker, Viktoria; Montellano, Felipe A.; Wiedmann, Silke; Rath, Dominik; Geisler, Tobias; Nieswandt, Bernhard; Kraft, Peter; Kleinschnitz, Christoph; et al.
Abstract: Patients with ischemic stroke (IS) are at increased risk of mortality and recurrent cerebro- or cardiovascular events. Determining prognosis after IS remains challenging but blood-based biomarkers might provide additional prognostic information. As platelets are crucially involved in the pathophysiology of vascular diseases, platelet surface proteins (PSP) are promising candidates as prognostic markers in the hyperacute stage. In this pilot study, feasibility of PSP analysis by flow cytometry (HMGB1, CD84, CXCR4, CXCR7, CD62p with and without ADP-stimulation, CD41, CD61, CD40, GPVI) was investigated in 99 (median 66 years, 67.5% male) acute IS patients admitted to Stroke Unit within a substudy of the Stroke-Induced Cardiac FAILure in mice and men (SICFAIL) cohort study. Association between PSP expression and unfavorable one-year outcome (cerebro- or cardiovascular event, all-cause mortality and care dependency defined as Barthel Index <60) was explored. PSP measurements were feasible. Several process- (e.g. temperatures, processing times) and patient-related factors (e.g. prestroke ischemic events, surgery, blood pressure, antiplatelet therapy) were identified to be potentially associated with PSP expression. Elevated CD40 levels above study population's median were associated with unfavorable outcome. Standardized conditions during blood draw and processing within the hyperacute stroke unit setting are required and patient-related characteristics must be considered for valid measurements of PSP. Trial registration : German Clinical Trials Register (DRKS00011615).